The impact of international law for the development of ecological democracy - Павлова, О. В. (Problems of legality, 2015)
This paper assesses the ecological democracy issues in the light of international law regulation. The concept of ecological democracy is developed through the principles of ecological democracy and consistency of the national legislation with international law.